DAMPAK AKUISISI DAN MERGER TERHADAP HARGA SAHAM, VOLUME PERDAGANGAN SAHAM DAN KINERJA PERUSAHAAN - Januar Eko Prasetyo (Akutansi Bisnis & Manajemen ( ABM ), 2002)
Acquisition and merger were to increase synergy, restructuring business, increase shareholder and management wealth. The objectives of this study is to test trading volume activity, stock price, and performance firm (before and after acquisition & merger). The study analyze 31 cases of acquisition and merger during 1995 - 1998 time period in Jakarta Stock Exchange. Data collected from Business Data Center, The Anatomy of the Indonesian Stock Exchange, and Indonesian Capital Market Directory. To test the hypothesis, this study employ Paired Sample t-test. The result of study show that acquisition and merger is no difference trading volume activity and stock price, but performance firm is difference.